The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3233/jad-150457
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Oximetry Imaging in Alzheimer’s Disease

Abstract: This is the first study of retinal oxygen metabolism in any central nervous system disease. It discovers abnormalities in retinal oxygen metabolism in AD. The findings are similar to those seen in age-related macular degeneration and diabetic retinopathy. Noninvasive retinal oximetry may offer new insights into pathophysiology of AD. Further studies are needed to confirm and expand these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 22 publications
5
52
0
1
Order By: Relevance
“…The use of spectrophotometric retinal oximetry measures oxygen saturation in blood vessels. Another study has confirmed that the retinal oxygen saturation in retinal arterioles and venules is significantly elevated (Einarsdottir et al 2015). Oxygen delivery is the product of the blood flow and the arteriovenous difference in oxygen concentration.…”
mentioning
confidence: 56%
“…The use of spectrophotometric retinal oximetry measures oxygen saturation in blood vessels. Another study has confirmed that the retinal oxygen saturation in retinal arterioles and venules is significantly elevated (Einarsdottir et al 2015). Oxygen delivery is the product of the blood flow and the arteriovenous difference in oxygen concentration.…”
mentioning
confidence: 56%
“…These changes include narrowed veins, reduction of blood flow, vascular attenuation, increased width variation, reduction of branching complexity and optimality, smaller fractal dimensions, and changes in tortuosity [19, 32, 50, 59, 183]. A recent study by Einarsdottir et al [49] reported that although vascular diameter was not changed, blood oxygen saturation was notably elevated in the AD retina with oximetry data closely matching that seen in AMD.…”
Section: Non-specific Ocular Abnormalities In Ad Patientsmentioning
confidence: 98%
“…Reports have indicated supranuclear and deep cortical cataracts, opacity due to increased light scattering, and other changes that may be associated with the findings of Aβ peptides in the lens [49, 69, 101, 102, 133]. On the other hand, a study that examined amyloidopathy in cortical cataracts was unable to detect Aβ in lenses of patients with and without AD [132].…”
Section: Non-specific Ocular Abnormalities In Ad Patientsmentioning
confidence: 99%
“…A significant 2.1-fold increase in retinal amyloid index (RAI), a quantitative measure developed to assess numerical value of amyloid burden in the retina of living patients, was revealed in AD patients versus matched controls (Figure 7L–M) [485]. Recent studies applying non-invasive retinal imaging in live AD patients, which detected NFL thinning [466, 477], increased inclusion bodies [554, 555], reduced blood flow, microvasculature alterations, and oxygen saturation in arterioles and venules [479, 556, 557], and importantly, hallmark Aβ deposits [485], are encouraging first steps towards the development of practical tools for predicting disease risk and progression. Since the retina in other ND such as multiple sclerosis, ischemic stroke, and Parkinson’s disease also exhibits pathophysiological processes similar to those detected in the brain [501, 558561], retinal imaging may also facilitate differential diagnosis for different proteinopathies, neurodegenerative and neurological diseases.…”
Section: Contribution and Role Of Retinal Imagingmentioning
confidence: 99%